FRESHCO: multiple implications of invasive species on freshwater mussel decline and coextinction processes - Teixeira, Amílcar (2017)
Freshwater mussels (FM) are among the most threatened faunistic groups worldwide. FM depend on fish to complete their life cycle, where mussel larvae (glochidia) use a specifíc range offish hosts. This trait makes them particularly threatened by invasive alien species (IAS) since changes on the host físh populations may eventually lead to the decline or co-extinction ofthe dependent species. The Iberian Península holds a high levei ofthreatened freshwater species, including físh and mussels. Furthermore, Iberian freshwater systems are among the most heavily invaded ecosystems in the world. Under those considerations, FRESHCO project aims to estimate the direct and indirect impacts of selected highly IAS belonging to distinct functional groups (from plants to vertebrates) on the native Iberian FM and its fish host fauna. Five tasks (T) will be executed: Tl will use fíeld and lab experiments to assess the possible competition between the IAS C. fl.uminea and native FM; T2 will be composed ofa series oflab experiments to assess host fish suitability of native FM; T3 will use molecular and classical detection tools to analyze the diets ofselected IAS and assess their predation on FM larvae, juveniles and adults; T4 will use a battery offíeld and lab experiments to assess the impact ofmassive annual die-offs ofthe invasive aquatic plant E. crassipes on the native FM; and in T5, 150 sites ofthe Douro river basin will be surveyed where mussel and fish assemblages and their habitats will be characterized, in arder to evaluate and distinguish the impacts of IAS and habitat degradation on the native fauna. From an ecological point of view, expected results from this project would help to elucidate the real impacts ofthe most prominent IAS on the threatened native FM and fish species in Iberia. From a management point ofview, this project will facilitate a more effective allocation ofresources spent on both native species conservation and IAS management.